Constraining the origin of sedimentary organic matter in the eastern Guangdong coast of China using δ13C and δ15N - Wu, Junwen; Chen, Jisheng; Wang, Cui; Yan, Xiuli; Yin, Xijie; Liu, Qian (Frontiers in Marine Science, 2023)
The source apportionment of organic carbon is of great scientific significance for understanding the carbon sink pattern in the coastal ocean. The concentrations of total organic carbon (TOC) and total nitrogen (TN) and their isotopic compositions (δ13CTOC and δ15NTN) were determined in surface sediments and sediment cores (Y3 and Y5) collected in the eastern Guangdong coast (EGDC) during spring, summer and winter cruises in 2021, in order to determine the distribution and source of sedimentary organic matter. Spatially, TOC and δ13CTOC distributions in the EGDC have contrasting patterns; TOC concentrations decreased and δ13CTOC values increased with distance offshore. Higher TOC concentrations and enriched δ13CTOC were observed in the marine aquaculture area off EGDC. The measured values of δ13CTOC, δ15NTN and the C/N ratio constrained the two dominant sources of organic matter, marine and terrestrial material, in the EGDC. Using a two end−member mixing model, we estimated the proportion of marine organic matter to be 74 ± 20% in spring, 74 ± 16% in summer and 75 ± 12% in winter, respectively. This suggests in situ production of marine phytoplankton dominated the organic carbon pool (average= 74%) in the EGDC sediment. These consistent marine organic matter contributions are also observed in sediment cores, with proportions averaging 59 ± 5% in core Y3 and 66 ± 4% in core Y5. The observed variations in biogeochemical proxies in sediments are thus mainly caused by differing relative contributions of marine and terrestrial organic matter. Additionally, the high TOC inventory in the marine aquaculture area indicates increased carbon storage and carbon fixation capacity compared to the other areas investigated. Overall, this study establishes a background carbon database in the coastal environment that can be used in future studies of blue carbon to achieve carbon neutrality in China.